Metagenomics and chemotherapy‐induced nausea: A roadmap for future research. Issue 3 (13th October 2021) - Crowder, Sylvia L.; Hoogland, Aasha I.; Welniak, Taylor L.; LaFranchise, Elizabeth A.; Carpenter, Kristen M.; Li, Daneng; Rotroff, Daniel M.; Mariam, Arshiya; Pierce, Christine M.; Fischer, Stacy M.; Kinney, Anita Y.; Dong‐Binh Tran, Thi; et al.
Abstract : Uncontrolled chemotherapy‐induced nausea and vomiting can reduce patients' quality of life and may result in premature discontinuation of chemotherapy. Although nausea and vomiting are commonly grouped together, research has shown that antiemetics are clinically effective against chemotherapy‐induced vomiting (CIV) but less so against chemotherapy‐induced nausea (CIN). Nausea remains a problem for up to 68% of patients who are prescribed guideline‐consistent antiemetics. Despite the high prevalence of CIN, relatively little is known regarding its etiology independent of CIV. This review summarizes a metagenomics approach to the study and treatment of CIN with the goal of encouraging future research. Metagenomics focuses on genetic risk factors and encompasses both human (ie, host) and gut microbial genetic variation. Little work to date has focused on metagenomics as a putative biological mechanism of CIN. Metagenomics has the potential to be a powerful tool in advancing scientific understanding of CIN by identifying new biological pathways and intervention targets. The investigation of metagenomics in the context of well‐established demographic, clinical, and patient‐reported risk factors may help to identify patients at risk and facilitate the prevention and management of CIN. Abstract : In this review, a comprehensive metagenomic approach is proposed for investigating genetic risk factors that encompasses both human (ie, host) and gut microbial genetic variation. An overview of current knowledge about chemotherapy‐induced nausea and vomiting, including the neurobiology, treatment, and associated risk factors, is described after a summary of genetic and gut microbial associations with chemotherapy‐induced nausea and other gastrointestinal toxicities.